The immune response of maternally immune chickens vaccinated with the Australian V4 Newcastle disease vaccine - Ibrahim, A. Latif; Chulan, U.; Ideris, Aini; Babjee, A. Mustaffa (1982)
Vaccination of congenitally immune chickens at 1 and 21 days old with the Australian V4 Newcastle disease vaccine by drinking water and intranasal methods induces variable degrees of antibody responses and resistance against challenge with virulent NDV. Vaccination of chickens at one day old failed to induce any stimulation of HI antibodies. A significant amnestic response was observed when the chickens were revaccinated at 21 days with 5 doses of the vaccine through drinking water. The chickens were not fully protected when challenge at 35 and 63 days old. The degree of protection declines with the age of the chickens. Chickens vaccinated by the drinking water method were better protected than chickens vaccinated intranasally.